The feeding of children from one to five years (London : His Majesty's Stationery Office)
1942-03 1942 1940s 24 pages 3 The amount of vitamin D in many foods is not yet known; the best sources are oils and fats, particularly fish liver oils, butter, modem margarine and eggs. It is also formed in the body when the skin is exposed to sunlight. A small dose daily, especially in winter, of cod, halibut or other fish liver oil or emulsion, according to the make and strength will ensure the provision of sufficient vitamin D to meet requirements especially of bone and tooth formations. A national brand of cod liver oil is now supplied to children under five. A concentrated source of vitamin C in the form of fruit juices is available under the same arrangement for children under two. Children over a year old may be assumed to be accustomed to potatoes mashed in gravy or milk, and to mashed vegetables, milk puddings and porridge. From about 15 months onwards they can be given small helpings of steamed puddings and gradually accustomed to unmashed vegetables, and later on, to salads. Fried foods and other fatty or spiced dishes are best avoided, though children over three years may be given fried bread, and children under three years bread dipped in bacon fat. Simple and well-balanced meals given at regular times and in a quiet atmosphere are best for the proper nutrition of children. Dietary rules and allowances for children aged 1 to 5 years. Allow 1 pint of milk or more per head daily. If pasteurised milk cannot be obtained, milk should be brought to the boil before use. One-third should be taken at breakfast; one-third at tea and the remainder can be used to make soups, sauces, puddings and custards and for a morning drink. Milk is specially rich in calcium and other salts which are necessary for the proper formation of bones and teeth. If liquid milk should become short, dried milk, if available, should be used for cooking. Full use should be made of the National Milk Scheme. Encourage children to drink at least ½-pint of water daily. All bread should be national wheatmeal and the flour used in cooking should be national wheatmeal. National wheatmeal bread makes excellent toast and rusks. Toast and rusks should be served daily to promote teeth eruption, mastication and salivation. Children should be taught to chew thoroughly. Salads, consisting of watercress, tomatoes, lettuce, swedes, cabbage, etc., should be given frequently when in season. Young children should be given them shredded or grated, and the amount increased gradually. Serve potatoes and vegetables, cooked or raw, at least once daily and preferably oftener. Vegetables should be as varied as possible and should include pulses, fresh, dried or canned, which are rich in protein. Potatoes should be cooked in their skins. The allowance of vegetables should be about one tablespoonful for children under two years and about two for children of five years of green or root vegetables. They should be mashed at first, but the children should be gradually accustomed to eat unmashed vegetables. Small helpings of finely shredded or grated raw vegetables should also be served frequently. In cooking vegetables attention should be paid to the rules for preserving the maximum nutrient value, as set out in Appendix III. Fresh fruit should be served when obtainable either raw or cooked. Dried fruits are valuable for cooked dishes and are useful as a preventive of constipation; they are also rich in vitamin B and salts. Liver, kidney and fish are rich in constructive and protective nutrients and should be served when obtainable. For children under 2 years the allowance at one meal should be about 1 oz. of meat, 1½ oz. fish, or ¾ oz. liver or kidney (raw weights), and it should be minced. As children grow older the allowances should be increased to about 127/NU/5/5/1/28